Heat Transfer Coefficients and Pressure Drops for R-134a and an Ester Lubricant Mixture in a Smooth Tube and a Micro-Fin Tube - Steven, Eckels J.; Doerr, Tom M.; Pate, Michael B. (ASHRAE, 1998)
This paper reports average heat transfer coefficients and pressure drops during evaporation and condensation of mixtures of R-134a and a 150 SUS penta erythritol ester branched-acid lubricant. The smooth tube and micro-fin tube tested in this study had outer diameters of 9.52 mm (3/8 in.). The micro-fin tube had 60 fins, a fin height of 0.2 mm (0.008 in), and a spiral angle of 18o . The objective of this study was: 1) to evaluate the effectiveness of the micro-fin tube with R-134a, and 2) to determine the effect of circulating lubricant. The experimental results show that the micro-fin tube has distinct performance advantages over the smooth tube. For example, the average heat transfer coefficients during evaporation and condensation in the micro-fin tube were 50% to 200% higher than those for the smooth tube, while the average pressure drops were on average only 10% to 50% higher. The experimental results indicate that the presence of lubricant degrades the average heat transfer coefficients during both evaporation and condensation at high lubricant concentrations. Pressure drops during evaporation increased with the addition of lubricant in both tubes. For condensation, pressure drops were unaffected by additions of lubricant.